2023
DOI: 10.3390/cosmetics10050128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hypoxic Chamber Training Series on Skin Characteristics of Overweight and Obese Women

Anna Grodecka,
Olga Czerwińska-Ledwig,
Adrianna Dzidek
et al.

Abstract: Obesity is a disease of civilization. The COVID-19 pandemic has caused an increase in its incidence; therefore, there is an increasing emphasis on programs aimed at improving body composition, often through physical activity. Various modifications to training interventions are being introduced, including the modification of the thermo-climatic conditions of the training. However, to date, whether such a modification is safe for the skin has not been studied. The purpose of this study was to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…For CON12, it was indicated that after 12 weeks of observation, BFP was significantly higher than before starting the project, which is a characteristic manifestation of the progression of obesity as a disease. Similar effects have been observed earlier [48], indicating the necessity of introducing interventions for obese individuals, as leaving them without any actions leads to disease progression.…”
Section: Discussionsupporting
confidence: 84%
“…For CON12, it was indicated that after 12 weeks of observation, BFP was significantly higher than before starting the project, which is a characteristic manifestation of the progression of obesity as a disease. Similar effects have been observed earlier [48], indicating the necessity of introducing interventions for obese individuals, as leaving them without any actions leads to disease progression.…”
Section: Discussionsupporting
confidence: 84%
“…Recent research findings indicate that training sessions conducted in hypoxic conditions contribute to increased fat tissue reduction and lower blood cholesterol levels [17,18,20], which has favorable implications for the treatment of obesity and related diseases. It is also shown that the training in hypoxic conditions is safe for the skin-it positively affects stratum corneum hydration, without significantly altering the function of the skin barrier or its firmness [21].…”
Section: Introductionmentioning
confidence: 99%